Media Framing and Audience Perception of Farmer/Herder Conflict in Nigeria: A Study of Newspaper Coverage of the Southern Taraba Crisis 2018-2022 - David Felix; Lingbuin Goodness Jigem; Linus M. Ngantem (Journal of Multidisciplinary Science: MIKAILALSYS, 2025)
This study examined media framing and audience perception of Farmer/Herder conflict in Nigeria with focus on newspaper coverage of the Southern Taraba Crisis 2018-2022. The study was anchored on the Framing Theory and the Social Responsibility Theory to provide a framework for analysis. This study used a qualitative research design with Content Analysis and Survey Method to gather data from 115 editions of two Nigerian newspapers, Vanguard and Daily Trust, published between 2018-2022. The population was chosen through purposive sampling, with a convenience sampling approach used to determine the sample size. Coding sheet was used for content analysis, focusing on media reports on farmers/herder’s conflict. Finding from the study revealed that newspaper coverage of the farmer/herder conflict in Nigeria predominantly employed conflict-escalating frames, such as ethnic blame, victimization, and inflammatory language. The study also found that audience perception of media coverage was largely negative, with many respondents viewing newspaper reporting as biased or sensational rather than balance and fair reporting. Further finding revealed that political pressure and media ownership were identified as the dominant factors shaping conflict coverage in Nigerian newspapers. The study concluded that media coverage played a dual role in either escalating or de-escalating conflicts, depending on the framing strategies employed. It is therefore, recommended among others that media organizations should prioritize peace journalism by emphasizing conflict-sensitive reporting that promotes dialogue, reconciliation, and de-escalation rather than sensationalism and ethnic blame.